Obstetricians Role in the Protection, Promotion and Support of Infant and Young Child Feeding - Tasnim, Saria (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Obstetricians have the privilege to serve the women during pregnancy, childbirth and beyond. This review is made to highlight obstetricians role in preparing women for breast feeding and complementary feeding as well as supporting them in case of any problem related with infant feeding. Bangladesh J Obstet Gynaecol, 2014; Vol. 29(2) : 102-105